Effects of annealing temperature and time on the structural and physicochemical properties of sweet potato flour hydrogels - Ziwen Zhang; Mengshan Shang; David Julian McClements; Chao Qiu; Na Ji; Lei Dai; Yang Qin; Liu Xiong; Qingjie Sun (Food Chemistry: X, 2023)
The physicochemical properties of sweet potato flour (SPF) can be modified by annealing. Native SPF was annealed in deionized water at a flour-to-water ratio of 1:3 (w/v) and temperatures of 50, 55, 60, or 65 °C for either 12 or 24 h. Annealed SPF maintained the A-type crystalline region and displayed increased relative crystallinity, increased pasting temperature, and decreased breakdown. SPF gels showed enhanced hardness together with better springiness when SPF was annealed at low temperature/long time or high temperature/short time. Annealed SPF hydrogel sheets contained larger, more uniform, and smoother pores than native ones. Noticeably, hydrogel sheets made of SPF annealed at 50 °C for 24 h exhibited advanced fracture strain from 93% to 176%. Overall, this work showed that annealing could modulate the characteristics of SPR hydrogels, which may widen the extent of applications in food industries. However, the annealing conditions need to be optimized.